Association of the efficiency of hemodialysis instruments in the removal of microbial and chemical pollutant - Shahriyari, Habib Allah; Jalil, Abduladheem Turki; Sarizadeh, Gholamreza; Shodmonova, Zebuniso R.; Takdastan, Afshin; Kiani, Fatemeh; Mohammadi, Mohammad Javad (Frontiers in Public Health, 2022)
Dialysis water is vital because of various harmful contaminants for patients. The aim of this study was to assess the efficiency of hemodialysis instruments in the removal of microbial and chemical pollutant in educational hospitals affiliated to Ahvaz Jundishapur University of medical sciences, Iran during 2018–2019. This cross-sectional descriptive research studied the microbial and chemical water quality of hemodialysis instruments in Razi, Sina, and Golestan hospitals in Ahwaz, Iran. 72 samples of microbial parameters and 24 samples of chemical parameters were collected from water used in hemodialysis instruments, including microbial characteristics (the total coliform, fecal coliform and heterotrophic bacteria counts) and chemical characteristics (pH, turbidity, PO4, Cl, Mg, So4, Ca, NO2, and EC) at Razi, Imam, and Golestan educational hospitals on all weekdays during 2018-2019. In this study, experiments were done according to the current standard methods, EPA from hemodialysis instruments. Finally, using SPSS18 software and descriptive statistics, the relationship between results at the removal of toxic, microbial, and chemical pollutants in different months and hospitals was investigated. this study showed that the average concentration of chemical characteristics during the warm season at Razi, Imam, and Golestan educational hospitals for pH, Turbidity, PO4, Cl, Mg, So4, Ca, NO2, and EC were (6.867, 6.4475, 6.53); (2.985, 3.035, 1.226); (0.075, 0.245, 0.195); (38.5, 21.965, 144.87); (1.552, 1.657, 39.445); (8.6, 4.5, 21.5), (2.09, 3.187, 78.975); (0.0082, 0.038, 0.155), and (125.25, 70.35, 78.35), respectively during 2018. Also, during 2019, results showed that the average levels of amounts for pH, Turbidity, PO4, Cl, Mg, So4, Ca, NO2, and EC in Razi, Imam, and Golestan educational hospitals were (7.077, 7.252, 6.435), (1.725, 0.595, 4.16), (0.0775, 0.0597, 0.0297), (52.33, 138.81, 20.92), (23.52, 18.227, 8.767), (35, 27.25, 4.05), (14.58, 28.152, 9.25), (0.0067, 0.0045, 0.0032), and (210.52, 121.62, 29.16), respectively. According to the results, hemodialysis instruments in Razi and Imam have a 90% efficiency in removing heterotrophic bacteria counts (HPC). Based on these findings, educational hospital hemodialysis equipment effluent in Ahvaz, Iran was mitted to Iran environmental standards for use in hemodialysis machines. The result showed that the removal percentage level of microbial and chemical pollutants by the hemodialysis process is comparatively suitable. It should be mentioned that in the proper operation and reconstruction, hemodialysis systems can have an increased rate of removal of microbial and chemical pollutants.